Regional Cooperation for Health, Science and Technology (RECOOP HST) Consortium - Vari, S.G. (Вiopolymers and Cell, 2011)
In 2006 Cedars–Sinai Medical Center (CSMC), Los Angeles, CA, USA with eleven Central and Eastern European (CEE) universities and academic organizations from six countries (Croatia, Czech Republic, Hungary, Romania, Slovak Republic, and Ukraine) formed the RECOOP HST Consortium.